Is Stress Levels And Coping Mechanism becomes factor that affected Challanging of Mother that have Children with Mental Retardation - Amar Akbar; Imam Zainuri (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Mental retardation is a weakness that occurs in intellectual function. With the burden faced by parents will be able to cause stress and will adversely affect their children if not using the right coping strategies. This study aims to identify the level of stress and coping mechanisms in mothers who have children with mental retardation. The research design used in this research is descriptive. The instrument used is questionnaire. The sample in this research are 30 mothers who have children with mental retardation with Primary School Extraordinary level (PSE) in SLB ACD Pertiwi Kota Mojokerto. Sampling with Total Sampling technique. From the results of this study showed that most respondents experienced moderate stress level as much as 17 respondents (56.7%). Most of the respondents aged 31-49 years as many as 16 respondents (53.3%). Most respondents use adaptive coping mechanism that is 27 respondents (90,0%). The results of the analysis indicate that the stress level of mothers who have children with mental retardation is still in the level of moderate stress. This is due to the influence of mothers with social support. The higher the social support the lower the level of stress experienced by the mother. Therefore respondents should make efforts to cope with stress by changing the problems encountered and expanding the source to overcome them. Keywords : Stress level, coping mechanism, mental retardation.